Altered states of leadership: mindfulness meditation, psychedelic use, and leadership development - Simonsson, Otto; Stenfors, Cecilia U. D.; Goldberg, Simon B.; Hendricks, Peter S.; Osika, Walter (Frontiers in Psychology, 2023)
Background: Previous research suggests that mindfulness meditation and psychedelic substances show promise as mental health interventions, but relatively little remains known about their potential impact on leadership outcomes. Aims: This study aimed to investigate if and how mindfulness meditation and psychedelic use may impact leadership among respondents with a management position as their primary role at work. Methods: Using samples representative of the US and UK adult population with regard to sex, age, and ethnicity (N=9,732), this study used quantitative and qualitative methods to examine if and how mindfulness meditation and psychedelic use may impact leadership. Results: Among respondents with a management position as their primary role at work (n = 3,150), 1,373 reported having tried mindfulness meditation and 559 reported having tried psychedelics. In covariate-adjusted regression analyses, both lifetime number of hours of mindfulness meditation practice and greater psychological insight during respondents’ most intense psychedelic experience were associated with a positive impact on leadership (ORs=2.33, 3.41; ps<.001), while qualitative analyses revealed nuances in the type of impacts mindfulness meditation and psychedelic use had on leadership. There were several subthemes (e.g., focus, creativity, patience, empathy, compassion) that were frequently reported with both mindfulness meditation and psychedelic use. There were also unique subthemes that were more commonly reported with mindfulness meditation (e.g., improved sleep, stress reduction, calming effects) and psychedelic use (e.g., greater self-understanding, less hierarchical attitudes toward colleagues, positive changes in interpersonal attitudes and behaviors), respectively. Conclusions: Although causality cannot be inferred due to the research design, the findings in this study suggest potential complementary effects of mindfulness meditation and psychedelic use on leadership, which could inspire new approaches in leadership development.